Strategi Adaptasi Perusahaan GPS Finance pada Kepatuhan Pajak Material PPH Pasal 21 Selama Masa Pandemi Covid-19 Tahun 2020/2021: Studi Kasus Kantor GPS Finance Medan - Putri, Egha Fierda; Arief, Muhammad; Rambe, Rizki Filhayati (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to find out how the GPS Finance company’s strategy in tax reporting on tax incentives during the pandemic to maintain company stability in the future and to determine the impact of the COVID-19 pandemic on PPh 21 tax compliance on GPS Finance. This research is a type of descriptive research, using data collection techniques by means of observation, interviews and documentation. In this study interviewed as many as 7 employees of GPS Finance Medan, as taxpayers with income above PTKP.Tax is a source of income for the state. Covid is an unavoidable pandemic. This pandemic has a touching impact on the country’s economy, so a strategy must be carried out so that taxpayer compliance can be realized properly. The phenomenon of a decrease in the number of mandatory income and income GPS Finance which causes the author to be interested in researching. The results of the study show that there is an impact on compliance with PPh 21 tax materials during the COVID-19 pandemic in the 2020/2021 case study of the GPS Finance Medan office. The government also helps taxpayers to maintain economic stability and emerge from the crisis during the pandemic, by issuing Covid-19 incentives for taxpayers in accordance with the requirements of "PPh article 21 borne by the government EKS PMK Number 9/PMK.03/2021".